Stoic partisans. The political conditioning of economic perceptions in Uruguay - Opertti, Martín (Revista Latinoamericana de Opinión Pública, 2020)
The power of the electorate to reward or to punish governments for their performance is one of the pillars of conventional democratic theory, with economic perceptions as one of the most important issues for the public opinion. However, there is an ongoing debate over whether causality also flows the other way. This article aims to test whether partisanship shapes economic perceptions while extending the argument to the context of a developing economy. Furthermore, it analyses the impact of not only the direction of partisanship but also it´s strength, an overlooked feature in the partisan bias literature. The analysis, which aggregates an unusually rich data set of Uruguayans´ economic evaluations for the 2001-2019 period, presents strong evidence for the argument that both the direction and strength of partisanship produce great bias in economic judgments even in a developing economy context where citizens are more vulnerable to economic shocks. These findings suggest a rather unsettling scenario for electoral accountability in a significant part of the Uruguayan electorate.